Pelagic early development of the silver grunt Pomadasys argenteus in Nakagusuku Bay, Okinawa, Japan, with notes on its occurrence and spawning patterns - Uehara, Masato; Chimura, Yoshizumi; Ohta, Itaru; Ebisawa, Akihiko; Miyaoka, Yuki; Tachihara, Katsunori (Discover Animals, 2025)
The silver grunt Pomadasys argenteus is an important coastal fishery resource for the Okinawa Islands of the Ryukyu Archipelago located in the northwestern Indo-Pacific. However, information on its life history, which is essential for management of fisheries, is limited. This study aimed to evaluate the early development, occurrence, sexual maturation, and reproductive cycle of P. argenteus , using specimens collected from Nakagusuku Bay, Okinawa Island, Japan. Larvae [4.33–9.24 mm body length (BL)] and pelagic juveniles (7.91–11.69 mm BL) of P. argenteus were distinguished from other haemulid species by the number of myomeres and dorsal fin rays, head spination, melanophore pattern and continuity, and distribution of other species in the same genus. Both larvae and juveniles were observed in the offshore epipelagic zone of the bay from April to August (excluding July), apparently corresponding to the spawning period. These observations suggested that the spawning season extends from spring to summer. Based on the relationship between fork length (FL) and gonadosomatic index, the minimum size at sexual maturity was estimated to be 28.7 cm FL for females and 22.9 cm FL for males, indicating that females are larger than males. These results suggest that P. argenteus is highly dependent on inner bay environments throughout its life history. This study offers insights into the morphological development of P. argenteus and underscores the ecological significance of inner bay areas, which serve as nursery grounds for the species.